Youth and gambling disorder: What about criminal behavior? - Mestre-Bach, Gemma; Granero, Roser; Vintró-Alcaraz, Cristina; Juve-Segura, Gerard; Marimon-Escudero, Mario; Rivas-Perez, Sandra; Valenciano-Mendoza, Eduardo; Mora-Maltas, Bernat; del Pino-Gutierrez, Amparo; Gómez-Peña, Mónica; Moragas, Laura; Fernandez-Aranda, Fernando; et al. (Addictive behaviors, 2021)
Background and aims: The commission of illegal acts has been associated with gambling disorder (GD). However, little is known about young adults with GD who commit GD-related crimes. Therefore, the main aim of this study was to compare sociodemographic, clinical, personality and psychopathological features among young adults with GD with and without a history of illegal behaviors. Our second aim was to analyze the specific associations between these factors through a path analysis. Methods: A total of 808 treatment-seeking young adults who met criteria for GD were assessed at a public hospital unit specialized in behavioral addictions. Participants completed self-reported questionnaires to explore GD, personality traits, and psychopathological symptomatology. Results: Of the total sample, 291 patients (36.0%) had committed GD-related offences. Illegal acts were related to younger age and unemployment status. Greater levels of psychopathology, as well as earlier GD onset, longer GD duration and greater GD severity were also associated with the presence of criminal behaviors. Differences in personality traits were also found between these two groups. Discussion and conclusions: The GD group with a history of illegal acts showed dysfunctional personality traits and higher levels of psychopathology. Therefore, specific GD treatments and harm reduction interventions should be designed for these patients.
Keywords: gambling disorder; criminal behavior; young adults; illegal acts; psychopathology; personality; JCR; Scopus